Seronegative paraneoplastic cerebellar degeneration: the PNS Euronetwork experience. (28th January 2014) - Ducray, F.; Demarquay, G.; Graus, F.; Decullier, E.; Antoine, J.‐C.; Giometto, B.; Psimaras, D.; Delattre, J.‐Y.; Carpentier, A. F.; Honnorat, J.
<x xml:space="preserve">Abstract</x> Background and purpose To describe the characteristics of patients presenting a paraneoplastic cerebellar degeneration without classical onconeural antibodies (seronegative PCD). Methods Thirty‐nine seronegative PCD patients from the Paraneoplastic Neurological Syndrome Euronetwork were retrospectively analyzed and compared with 180 patients with PCD associated with classical onconeural antibodies (seropositive PCD). Results No patient had anti‐CASPR2 or anti‐mGluR1 antibodies. No significant difference between the clinical characteristics of seronegative and seropositive PCD patients was observed. Yet the frequency of associated tumors was different. Lymphoma was more frequent in seronegative than in seropositive women (24% vs. 2%, P = 0.002) whilst gynecological cancer were less frequent (38% vs. 74%, P = 0.002). In comparison with seropositive men, seronegative men more frequently had a non‐small‐cell lung cancer (27% vs. 6%, P = 0.08) or a genitourinary cancer (22% vs. 0%, P = 0.04) but less frequently a small‐cell lung cancer (23% vs. 74%, P = 0.002). Seronegative and seropositive PCD patients with similar tumors had a similar overall survival. Conclusion The clinical characteristics of seronegative and seropositive PCD are similar but the spectrum of associated tumors is different. The immunological scenario of seronegative PCD seems to be different from that of limbic encephalitis with only few patients harboring anti‐neuropile antibodies.